Cardiological Society of India Practice Guidelines for Angiography in Patients with Renal Dysfunction - Bhandari, S. (Indian Heart J, 2012)
The potential risk of contrast-induced acute kidney injury (CI-AKI) has made utilization of coronary angiography in the work-up for the diagnosis of coronary artery disease in CKD quite low.(1) This is in contrast to increasing prevalence and severity of CAD as the serum creatinine rises.(2) In fact most CKD patients will succumb to CAD and not to ESRD.(3) Thus the judicious use of CAG/PCI in this setting is of prime importance but underused. The CSI began to develop guidelines for Indian context as most guidelines are those developed by ACC/AHA or ESC. The aim was to assist the physicians in selecting the best management strategy for an individual patient under his care based on an expert committee who would review the current data and write the guidelines with relevance to the Indian context. The guidelines were developed initially in June 2010 as an initiative of Delhi CSI. Three interventional cardiologist (SB, AS, KKS), one nephrologist (SCT) and two clinical cardiologists (ST, RG) along with Dr. Roxana Mehran (New York) and Dr. Peter McCullough (Missouri), U.S.A.; were involved in a three-way teleconference to discuss/debate the data. This was presented by SB, and over the next two hours each data subset was debated/agreed/deleted and this resulted in the “Guidelines for CAG in Renal Dysfunction Patients”. These were then written and re- circulated to all for final comments. Further, these guidelines were updated and additional Task Force Members nominated by Central CSI were involved in the formation of the final CSI Guidelines. Both (Roxana Mehran and Peter McCullough) reviewed these updated Guidelines in October 2012 and after incorporating the views of all the Task Force members—the final format is as it is presented in this final document.